The Role of Islamic Eucation in The Formation of The Character ‎and Morals of The Younger Generation ‎ - Lina Luthfiyyah; Siti Nafisatur Rohmah‎; Miftahur Rohmah; Muhammad Yusron Maulana El-Yunusi (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Islamic education plays an important role in shaping the morals and ethics of every human being, including the current generation. Religious education builds moral awareness, strengthens beliefs, and guides good behaviour through the understanding and practice of Islamic teaching. Values such as justice, honesty, courtesy, patience and generosity are taught to shape good character. Islamic educators also teach universal values such as respecting and valuing others and protecting the environment. Islamic education has a significant role in producing a high quality generation. So that the role of Islamic education in shaping the character and morals of the younger generation is to guide in moral formation in terms of moral formation, strengthening faith and worship, developing social awareness in the community, improving negative morals in the present, and teaching universal values such as discipline, having respect and hight responsibility and so on. This research uses a library research approach that focuses on encyclopedia, articles, and journals. It aims to instill the principles of character and morals. And also analyze the role that Islamic education playsin fastering character in the younger generation.